β-cell mitochondria in diabetes mellitus: a missing puzzle piece in the generation of hPSC-derived pancreatic β-cells? - Abdoulaye Diane (14152749) (2022)
Diabetes mellitus (DM), currently affecting 463 million people worldwide is a chronic disease characterized by impaired glucose metabolism resulting from the loss or dysfunction of pancreatic β-cells with the former preponderating in type 1 diabetes (T1DM) and the latter in type 2 diabetes (T2DM). Because impaired insulin secretion due to dysfunction or loss of pancreatic β-cells underlies different types of diabetes, research has focused its effort towards the generation of pancreatic β-cells from human pluripotent stem cell (hPSC) as a potential source of cells to compensate for insulin deficiency. However, many protocols developed to differentiate hPSCs into insulin-expressing β-cells in vitro have generated hPSC-derived β-cells with either immature phenotype such as impaired glucose-stimulated insulin secretion (GSIS) or a weaker response to GSIS than cadaveric islets. In pancreatic β-cells, mitochondria play a central role in coupling glucose metabolism to insulin exocytosis, thereby ensuring refined control of GSIS. Defects in β-cell mitochondrial metabolism and function impair this metabolic coupling. In the present review, we highlight the role of mitochondria in metabolism secretion coupling in the β-cells and summarize the evidence accumulated for the implication of mitochondria in β-cell dysfunction in DM and consequently, how targeting mitochondria function might be a new and interesting strategy to further perfect the differentiation protocol for generation of mature and functional hPSC-derived β-cells with GSIS profile similar to human cadaveric islets for drug screening or potentially for cell therapy. Other Information Published in: Journal of Translational Medicine License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12967-022-03327-5